Diagnosis of gestational diabetes mellitus: Comparison between national diabetes data group and carpenter- coustan Criteria - Dittakarn Boriboonhirunsarn (2018)
© 2013 is published by the Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand. Background: A 100-g oral glucose tolerance test (OGTT) is commonly used to diagnose gestational diabetes mellitus (GDM). Carpenter-Coustan (CC) criteria, based on lower threshold plasma glucose values than the National Diabetes Data Group (NDDG) criteria, result in an apparently increased prevalence of GDM. However, the extent of the increase is not known, and effects on perinatal outcome are not clear. Asian BiomedicineObjective: To evaluate the increase in the prevalence of GDM if CC criteria are applied to OGTT results, we compared findings with NDDG criteria. Pregnancy outcomes between women without GDM and those with GDM diagnosed by NDDG and CC criteria were compared.Methods: A total of 640 at-risk pregnant women were studied. They were either diagnosed as having GDM by initial testing (145 women), or repeat testing at 24-28 weeks of gestation (495 women). CC criteria were applied to the OGTT results and prevalence of GDM was re-evaluated.Results: The apparent prevalence of GDM increased by 22.2% using CC criteria. The change was 27.6% at the initial test and 31.5% at repeat tests during 24-28 weeks of gestation. Infant birth weight in GDM diagnosed by either NDDG or CC criteria was significantly higher than in the negative OGTT group (P < 0.001). Rates of macrosomia were comparable. Neonatal hypoglycemia was 14.6% in the NDDG group, 8.2% in CC only group, and 4.6% in negative OGTT group (P < 0.001).Conclusion: The CC criteria identify 22% more cases of GDM than NDDG criteria during initial and repeat tests.